2007
DOI: 10.1002/app.25932
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular weight on spherulitic growth rate of poly(ϵ‐caprolactone) and poly(ϵ‐caprolactone)‐b‐poly(ethylene glycol)

Abstract: The spherulitic growth rates of a series poly (e-caprolactone) homopolymers and poly(e-caprolactone)-bpoly(ethylene glycol) (PCL-b-PEG) block copolymers with different molecular weights but narrow polydispersity were studied. The results show that for both PCL homopolymers and PCL-b-PEG block copolymers, the spherulitic growth rate first increases with molecular weight and reaches a maximum, then decreases as molecular weight increases. Crystallization temperature has greater influence on the spherulitic growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 57 publications
2
23
1
Order By: Relevance
“…When T c,1 is close to T c,2 , two kinds of crystallization may start simultaneously to yield a cooperative morphology formation (lower route in Fig. 7) [46][47][48][49][50][51][52][53][54][55]. In PCL-b-PEO diblock copolymers, for example, the crystallizable temperature of PCL blocks is comparable to that of PEO blocks, and very unique crystalline morphologies, such as a concentric spherulite consisting of PCL cores and PEO coronas, are sometimes observed [46,47,49].…”
Section: Sequential Crystallization Of Crystalline-crystalline Diblocmentioning
confidence: 95%
“…When T c,1 is close to T c,2 , two kinds of crystallization may start simultaneously to yield a cooperative morphology formation (lower route in Fig. 7) [46][47][48][49][50][51][52][53][54][55]. In PCL-b-PEO diblock copolymers, for example, the crystallizable temperature of PCL blocks is comparable to that of PEO blocks, and very unique crystalline morphologies, such as a concentric spherulite consisting of PCL cores and PEO coronas, are sometimes observed [46,47,49].…”
Section: Sequential Crystallization Of Crystalline-crystalline Diblocmentioning
confidence: 95%
“…The complex interaction between structure, molecular constitution, and configuration as well as the local molecular mobility determines the crystallization kinetics [ 12 , 13 , 14 , 15 , 16 ]. The complexity of the polymer crystallization becomes evident if the crystallinity, the crystal size, and the melting temperature are discussed as a function of the crystallization temperature [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cooling thermograms for 5k5k, 5k10k, 5k16.3k, and 5k24.5k PEO-b-PCL are shown in Figure 1. The first peak is assigned to PCL crystallization because of its larger weight fraction, [17][18]21,[23][24][25][26][27][28][29][30][31][32][33][34][35] and therefore the second peak (indicated by arrows) was assigned to PEO crystallization. Onset Txs were determined for both PCL and PEO using Pyris software.…”
Section: Dsc Resultsmentioning
confidence: 99%
“…These morphologies match well with other reports of PEO-b-PCL, where PEO crystallization is not obvious via POM but was identified using techniques such as FTIR, XRD, or DSC. [17][18]21,[23][24][25][26][27][28][29][30][31][32][33][34] Films cast from toluene (Figures 4b, 4f, and 4j) show little-to-no birefringence. Because there is evidence for crystallization of both blocks in the FTIR spectra (Figure 3), it was concluded that crystals in films cast from toluene were preferentially flat-on instead of edge-on.…”
Section: Film Morphologymentioning
confidence: 99%
See 1 more Smart Citation